Decision Support Strategies for Hip and Knee Osteoarthritis: Less Is More. (18th September 2019) - Sepucha, Karen; Bedair, Hany; Yu, Liyang; Dorrwachter, Janet M.; Dwyer, Maureen; Talmo, Carl T.; Vo, Ha; Freiberg, Andrew A.
Abstract : Background: As guidelines and payers increasingly recommend use of patient decision aids (DAs), evidence about the comparative effectiveness of available DAs is critical for organizations interested in implementing them. The primary purpose of this study was to compare 2 DAs with regard to their ability to help patients become informed and receive their preferred treatment (that is, make an informed patient-centered decision), shared decision-making, surgical rates, and surgeon satisfaction. Methods: We performed a multisite factorial randomized trial enrolling patients with hip or knee osteoarthritis. Patients were randomly assigned to use a long, detailed DA (long DA) or short, interactive DA (short DA). Eight surgeons were randomly assigned to receive a patient preference report detailing the patient's goals and treatment preferences or to administer usual care. Results: We distributed 1, 636 pre-visit surveys, 1, 220 of which were returned (75% response rate), and 1, 124 post-visit surveys, 967 of which were returned (86% response rate). The patients in the sample had a mean age (and standard deviation) of 65 ± 10 years, 57% were female, 89% were white non-Hispanic, and 67% had knee osteoarthritis. The majority (67.2%) made informed patient-centered decisions, and the rate did not vary significantly between the DA groups (p = 0.97) or between the surgeon groups (p = 0.23). Knowledge scores were higher for the short-DA group (mean difference = 9%; p < 0.001). More than half of the sample (60.5%) had surgery within 6 months after the visit, and rates did not differ significantly by DA or surgeon group. Overall, the surgeons were highly satisfied and reported that the majority (88.7%) of the visits were of normal duration or shorter. Conclusions: The DECIDE-OA study is, to our knowledge, the first randomized comparative effectiveness study of 2 orthopaedic DAs. The short DA outperformed the long DA with regard to knowledge scores and was comparable with respect to other outcomes. The surgeons reported high satisfaction and normal visit duration with both DAs. Clinical Relevance: Surgeons need to ensure that patients with osteoarthritis are well-informed and have a clear preference regarding whether to undergo hip or knee replacement surgery. The DAs used in this study may help surgeons involve patients in elective surgery decisions and meet the requirements of informed consent.